Biological activity of hydroxyanthraquinones and their glucosides toward microorganisms - Cudlín, J; Blumauerová, M; Steinerová, N; Matêjů, J; Zalabák, V (Folia microbiologica, 1976)
Five mono- and dihydroxyanthraquinones as well as 12 of their glucosides (both free and acetylated) were tested with six different microbial species using the plate-diffusion method. None of the tested substances was active against Escherichia coli, 15 of the 17 substances displayed an activity toward Bacillus subtilis, Bacillus cereus, Candida albicans, Saccharomyces cerevisiae and Streptomyces aureofaciens. Relationships between the substance type and biological activity are discussed.
Keywords: glukosidy; Anthraquinones; Bacillus subtilis; Fungi; glykosidy; houby; Escherichia coli; Streptomyces aureofaciens; Chemical Phenomena; Chemistry; anthrachinony; Glycosides; Saccharomyces cerevisiae; Glucosides; chemické jevy; Candida albicans; Bacteria; Bacillus cereus; chemie